Merging Cases For Children In Conflict With The Law - Suwanto Putra, Steinly; Fatmawati Octarina, Nynda (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims is to describe the problem of legal protection for children, both from a criminal and civil perspective. By identifying differences and weaknesses in existing protection systems, this research seeks to provide an in-depth look at the steps that need to be taken to improve the situation. The research method used in this research is judicial normative with primary sources from journals regarding child protection as well as positive legal products on legal protection for children, especially children in conflict with the law. Legal ideology regarding children in Indonesia still shows differences in approach at various levels and legal domains. The implementation of the law to children and the role of parents as guardians and protectors of children do not yet have sufficient clarity. This condition places children in a very vulnerable position, where protection of their rights and welfare is often not optimal. The role of parents in protecting children is still limited, and the state has not standardized their role or provided adequate space to help children face legal problems.